"ACCEPT FROM ME, THE SERVANT OF YOUR GRACE, THIS BEAST." FROM THE HISTORY OF THE HUNTING CRAFT IN THE COSSACK HETMANATE IN THE END OF THE 17TH CENTURY - Сокирко, Олексій (Київський національний університет імені Тараса Шевченка, 2023)
Background. Hunting occupied an important place in the economies and socio-cultural life of pre-modern societies. Hunting and hunting culture in the Cossack Hetmanate were replicas of those traditions and practices that were formed within the framework of the cultural model of the Polish-Lithuanian Commonwealth. If trapping was traditionally an independent segment of the economy that provided food rations with additional products, then hunting was to a greater extent a courtly entertainment of the nobility that emphasized their social status and material capabilities. Methods. The research is based on the cataloging of all references to hunting, which are contained in the correspondence of Cossack and Mercenary Officials with Hetmans of the last quarter of the 17th century. The collected material is divided into thematic blocks (seasonality, hunting tools, etc.) and each of them is analyzed. The textological method in the analysis of correspondence shows the social symbolism of hunting and hunting gifts.  Results. The article presents a reconstruction of the hunting activities of Hetman’s mercenaries (kompanijci), which played a supporting role in their welfare and at the same time were training military practices. The range and seasonality of hunting coincided with the forest-steppe strip of the Dnieper region, where the kompanijci carried out their duty to guard the borders. The main objects of hunting were the so-called "red beast" - boar, moose, wolves, foxes. In addition to hunting, the mercenaries also practiced fishing, which supplied valuable products of the Dnieper ichthyofauna - sturgeon, pike, zander, and caviar. Meat and fur of wild animals, which were the object of hunting, had a high status of "knightly" products in the kitchen and everyday life of the Hetmanate. In the correspondence of mercenary officers with the commanders of mercenary regiments, hunting and hunting trophies were important as a way of obtaining status gifts, which representatives of the Cossack nobility exchanged among themselves. Disussion and conclusions. The exchange of hunting gifts marked a complex system of patronage and client networks that formed in the Hetmanate in the end of the 17th century. They reached the lowest floors of the officials hierarchy, whose members were the organizers of hunting sessions, and ended with hetmans, colonels and church hierarchs, as recipients of status gifts. The model of hunting industries based on the our reconstruction allows to extrapolate it to the functioning of hunting and the practices of exchanging hunting trophies as status gifts, and to other regions of the Cossack Hetmanate. DOI: https://doi.org/10.17721/1728-2640.2023.156.6

Вступ. Мисливство та полювання займали важливе місце в економіках та соціокультурному житті домодерних суспільств. Мисливський промисел та культура полювання в Гетьманщині були репліками тих традицій і практик, котрі сформувалися в рамках культурної моделі Речі Посполитої. Якщо мисливство традиційно було самостійним сегментом економіки, що забезпечував харчовий раціон додатковими продуктами, то полювання більшою мірою було куртуазною розвагою знаті, що підкреслювала її соціальний статус і матеріальні можливості. Методи. В основу дослідження покладено катологізацію всіх згадок про мисливство, які містяться в листуванні старшин найманих і козацьких полків з гетьманами останньої чверті XVII ст. Зібраний матеріал розподілено по тематичних блоках (сезонність, засоби полювання тощо) і проаналізовано кожен з них. Текстологічний метод при аналізі листування виявляє соціальну символіку мисливства та мисливських дарів. Результати. У статті подано реконструкцію мисливських занять гетьманських найманих жовнірів (компанійців), що відігравали допоміжну роль в їх економічному становищі й водночас були тренувальними воєнними практиками. Ареал і сезонність полювань збігалися з лісо-степовою смугою Придніпров’я, де компанійці несли свою службу з охорони кордонів. Головними об’єктами промислу був т. зв. червоний звір: вепр, лось, вовки, лисиці. Крім мисливства, компанійці також практикували рибальство, яке постачало цінні продукти дніпровської іхтіофауни – осетра, щуку, судака, кав’яр. Дичина та хутро диких тварин, які були об’єктом полювання, мали високий статус "лицарських" продуктів у кухні та побуті Гетьманщини. В листуванні компанійських старшин із командирами найманих полків полювання й мисливські трофеї мали важливе значення як спосіб отримання статусних подарунків (дичина й хутро), якими представники козацької знаті обмінювалися між собою. Дискусія та висновки. Обмін мисливськими дарами маркував складну систему патронально-клієнтарних мереж, які сформувалися в Гетьманщині наприкінці XVII ст. Вони сягали найнижчих поверхів старшинської ієрархії, члени якої були організаторами мисливських промислів, і завершувалися гетьманами, полковниками й церковними ієрархами як реципієнтами статусних подарунків, котрими були дичина та риба. Відтворена модель мисливських промислів на прикладі компанійців дає змогу екстраполювати її на функціонування мисливства й практик обміну мисливськими трофеями як статусними дарами й на інші регіони Гетьманщини. DOI: https://doi.org/10.17721/1728-2640.2023.156.6
"Який то звір нехай буде од мене, слуги вашої милості, ласкаве прийнятий". З історії мисливського промислу в Гетьманщині кінця XVII століття
Keywords: мисливство; полювання; Гетьманщина; Річ Посполита; козацька старшина; соціальні мережі; компанійці; історія; hunting; Cossack Hetmanate; Polish-Lithuanian Commonwealth; Cossack Officials; social networks; mercenaries